2019
DOI: 10.1039/c9nj02196e
|View full text |Cite
|
Sign up to set email alerts
|

The formation and physicochemical properties of PEGylated deep eutectic solvents

Abstract: Polymer PEG was used to form eutectic molecular liquids with hydrogen bonding acceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Diferuloylmethane (Curcumin), important bioactive component, is a natural phenolic compound derived from the spice turmeric (Curcuma longa). Many studies have shown that this compound can be used in a large variety of applications such as pharmacology for its anticancer, antimutagenic, antibacterial, anti‐inflammatory, antifungal, anti‐allergy, and antioxidant features . Lipophilic properties of curcumin lead to its low aqueous solubility and poor bioavailability, resulting in high rate of digestion and fast removal from the body .…”
Section: Introductionmentioning
confidence: 81%
“…Diferuloylmethane (Curcumin), important bioactive component, is a natural phenolic compound derived from the spice turmeric (Curcuma longa). Many studies have shown that this compound can be used in a large variety of applications such as pharmacology for its anticancer, antimutagenic, antibacterial, anti‐inflammatory, antifungal, anti‐allergy, and antioxidant features . Lipophilic properties of curcumin lead to its low aqueous solubility and poor bioavailability, resulting in high rate of digestion and fast removal from the body .…”
Section: Introductionmentioning
confidence: 81%
“…Previous reports also suggested that the increasing cathode dissolution at high temperature could be attributed to the decreased viscosity at higher temperature. 36,43 However, while the temperature is higher than 100 °C (e.g., 120 °C), the Co concentration is decreased, which might be mainly due to the reason that the escape rate of the LCO compound from DESs is higher than the dissolving rate. Therefore, although the mass transfer is improved and viscosity is decreased at 120 °C, the Co concentration decreases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…DESs were prepared according to the methods reported previously. [ 24b,28 ] In order to synthesize DES, a certain molar ratio (4: 1 or 2: 1) of HBD (PEG 200 or glycerol) and HBA (choline chloride) was mixed and then heated at 80°C under continuous stirring until a homogeneous and transparent liquid was formed. The obtained DESs were used in reactions without any purification.…”
Section: Methodsmentioning
confidence: 99%